PENGGUNAAN SKALA STROKE SYIAH KUALA PADA PENDERITA STROKE SEBAGAI METODE DIAGNOSIS YANG CEPAT DAN AKURAT - Syahrul*, Dessy R Emril*, Endang Mutiawati*, Suherman* (NEURONA, 2010)
INTRODUCTION THE COMPUTED TOMOGRAPHY SCAN IMAGE IS A CONSISTENT GOLDEN STANDARD IN DETERMINING DIAGNOSIS THE KIND OF STROKE THE COMPUTED TOMOGRAPHY SCAN FACILITY AT THE ZAINOEL ABIDIN PUBLIC HOSPITAL BANDA ACEH IS ONLY AVAILABLE VERY RECENTLY WHILE HEALTH DELIVERY FACILITIES IN THE DISTRICTS AND TOWNSHIPS IN THE PROVINCE OF ACEH DO NOT YET HAVE SUCH AN IMPORTANT FACILITY